Popular Resistance and Political Conformity in Nigeria’s Democratic Decline: A Historical Analysis of EndSARS and The VeryDarkMan Phenomenon - Filibus, Yaweh; Anjugu Joseph, Reuben; Andy Saleh, Saleh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article investigates how civic resistance and political conformity intersect in Nigeria's evolving democratic parlance, with a focus on the 2020 EndSARS protests and the digital activism of Martins Vincent Otse, popularly known as VeryDarkMan. The study aims to understand how ordinary citizens negotiate political space in response to state repression and institutional failure. Employing a historical-analytical method, the paper draws upon secondary sources, digital media content, and public discourse to examine the patterns, tactics, and implications of both street and online resistance. It traces the lineage of political protest from anti-colonial movements to contemporary digital activism, identifying how new forms of engagement challenge or adapt to authoritarian tendencies within Nigeria’s democracy. The findings reveal that while EndSARS marked a watershed in youth-led mobilisation, the state’s coercive response exposed the fragility of civil liberties under democratic rule. In its aftermath, digital figures like VeryDarkMan emerged as alternative voices, using social media to critique governance and amplify civic demands. However, the commodification of activism and state pushback have complicated these efforts. The study concludes that popular resistance in Nigeria continues to oscillate between protest and survival, shaped by both historical memory and digital innovation.